Efektifitas Pembentukan Pengadilan Hak Asasi Manusia (HAM) Tingkat ASEAN Oleh Asean Intern-Governmental Commision On Human Rights (AICHR) - Yogi Syahputra Al Idrus; Ilham Rusadi Abdullah; Tinuk Dwi Cahyani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Human Rights (HAM) is a value that is very essential since humans are born into the world which in everyday life has a natural nature attached to every individual whenever and wherever so that concretization through law becomes a repressive and preventive effort to pay attention, respect, appreciate and uphold it. Efforts to uphold human rights have been since 2009 the AICHR Court was formed through the 15th Summit as a human rights commission at the ASEAN level, until now the effectiveness of the performance of AICHR is still far from perfect because there have been cases that occurred in several ASEAN countries such as the Philippines, Indonesia, Malaysia, and Cambodia. This was not responded to at all by the AICHR court itself because the main function of AICHR is to protect and promote it in the form of protection at the ASEAN level so that it cannot assimilate and resolve cases that occur. Therefore the author sets out concretely two perspectives on how far the effectiveness and consequences of establishing the AICHR human rights court at the ASEAN level are. First, what are the causes of AICHR's ineffectiveness in upholding human rights in Southeast Asia? These two problems can be examined doctrinally and normatively conceptually to produce the following findings: firstly the lack of commitment from each ASEAN country to human rights, secondly the principle of non-intervention from each country so that decision making is based on consensus.